Clinical Response of Meropenem versus Meropenem and Azithromycin in Extensively Drug-Resistant Salmonella - Muhammad Ameen; Ali, Sundus; Ashraf, Jawad; Ikram, Naaz; Siddiqi, Ayesha; Naseer, Asif (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To compare the clinical response of Meropenem versus a combination of Meropenem and Azithromycin in Extensively Drug-Resistant Salmonella. Study Design: Quasi-experimental study. Place and Duration of Study: Tertiary Care Hospital, Malir Pakistan, from Mar to Sep 2023. Methodology: A total of 100 patients (50 in the Meropenem group and 50 in the Meropenem and Azithromycin group) who were diagnosed with typhoid fever secondary to extensively drug-resistant salmonella were included. The duration of hospital stay, post-therapy C-reactive protein, time for defervescence, and complete clinical response were compared between the groups. Results: Median age was 29(49–16) years. There were 78(78%) males and 22(22%) females. Median weight of patients was 75(90–55) kg. Median duration of fever was 6(14–1) days. Median baseline C-reactive protein was 44(167–13) mg/dl. Complete clinical response in Meropenem alone group 49(98%) was significantly higher as compared to Meropenem + Azithromycin group 38(76%), (p=0.001). Similarly, duration of hospital stay and time to defervescence were also significantly shorter in the Meropenem alone group (p<0.001). Conclusion: Meropenem alone is better than the combination of Meropenem + Azithromycin, with a shorter hospital stay, lesser time to defervescence, and better clinical response.